Electrochemical studies of certain 1-(toluenyl sulfonyl )-3- amino -4-(4’-substituted aryl hydrazono )-2-pyrazolin -5-ones (2011)
The electrochemical behavior of certain1-(Toluenyl sulfonyl)-3-amino-4-(4’-substituted aryl hydrazono)-2-pyrazolin-5-ones were studied at the droppingmercury electrode by employing DC polarography.The variables that influencethe electrode process were extensivelystudied. All compounds under investigationgave two well-defined polarographicwaves. The mechanism for the electrodeprocess was proposed in acid as well asin basic media.